EAST-WEST DICHOTOMY: A STUDY OF ORHAN PAMUK’S NOVELSILENT HOUSE - Umar Mushtaq (RADJA PUBLIKA, 2023)
Geographically and linguistically, Turkey has been at the core of the debate surrounding the conflict between East and the West and subsequently between the West and the Islamic world. Orhan Pamuk characterises Turkey as a